2012
DOI: 10.1093/humrep/des328
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bisphenol A concentrations and early reproductive health outcomes among women undergoing IVF

Abstract: The findings and conclusions in this report are those of the authors and do not necessarily represent the views of the Centers for Disease Control and Prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(146 citation statements)
references
References 50 publications
(61 reference statements)
6
134
1
5
Order By: Relevance
“…To test the hypothesis whether high estradiol levels were associated with worse oocyte, fertilization and peri-implantation parameters and early pregnancy outcomes in IVF, we decided to use similar methodology to establish our cut off to discriminate between the study (high estradiol) and control (lower estradiol) groups. The study outcomes included percentage of normal fertilization {defined as number of 2 pronuclei embryos/ number of matured oocytes (MII); MII oocytes were determined on the day of oocyte retrieval prior to injection for ICSI cycles, and~16-18 h following retrieval for conventional IVF cycles [26]}, proportion of embryos that developed to 6-8 cell stage on day 3 (number of 6-8 cell embryos/total number of 2 pronuclei embryos), positive pregnancy test (positive hCG 12-14 days following embryo transfer), biochemical pregnancy [defined as positive hCG without a gestational sac], implantation rate [defined as number of gestational sacs/number of embryos transferred], clinical pregnancy rate (documented intrauterine pregnancy with fetal heart activity), and first trimester spontaneous miscarriage [defined as pregnancy failure after visualization of intrauterine gestation sac].…”
Section: Methodsmentioning
confidence: 99%
“…To test the hypothesis whether high estradiol levels were associated with worse oocyte, fertilization and peri-implantation parameters and early pregnancy outcomes in IVF, we decided to use similar methodology to establish our cut off to discriminate between the study (high estradiol) and control (lower estradiol) groups. The study outcomes included percentage of normal fertilization {defined as number of 2 pronuclei embryos/ number of matured oocytes (MII); MII oocytes were determined on the day of oocyte retrieval prior to injection for ICSI cycles, and~16-18 h following retrieval for conventional IVF cycles [26]}, proportion of embryos that developed to 6-8 cell stage on day 3 (number of 6-8 cell embryos/total number of 2 pronuclei embryos), positive pregnancy test (positive hCG 12-14 days following embryo transfer), biochemical pregnancy [defined as positive hCG without a gestational sac], implantation rate [defined as number of gestational sacs/number of embryos transferred], clinical pregnancy rate (documented intrauterine pregnancy with fetal heart activity), and first trimester spontaneous miscarriage [defined as pregnancy failure after visualization of intrauterine gestation sac].…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, in a study performed by Knez et al (2014), which confirms changes to the semen quality of men with a determined environmental level of BPA, undisrupted development of embryos into blastocysts is described. As against this finding, in women who have undergone IVF, a correlation has been demonstrated between the concentration of BPA in urine and a change to the formation of blastocysts, though a reduced quality of embryos was not recorded (Ehrlich et al 2012). …”
Section: Influences Of Bpa On Reproduction Of Femalesmentioning
confidence: 99%
“…Furthermore, review of the literature did not demonstrate any association with oocyte quality, fertilization rate, embryo development, or ultimately the pregnancy rate for women embarking on IVF treatment (170). Human and animal studies demonstrated impaired steroidogenesis in granulosa cells exposed to BPA (52), and this is borne out by women with higher serum BPA concentrations undergoing IVF treatment whereby they have a lower peak estradiol concentration and reduced oocyte yield (39,94). A recent study of hair mercury concentrations, a marker of dietary fish intake, in women undergoing IVF treatment did not find a relationship between mercury levels and ovarian responsive to stimulation, oocyte fertilization rate, embryo development, and pregnancy rates (376).…”
Section: Pollutantsmentioning
confidence: 99%